Neuropsychological predictors of vocational rehabilitation outcomes in individuals with major depression: A scoping review - Bergdolt, Juliane; Sellin, Pauline; Driessen, Martin; Beblo, Thomas; Dehn, Lorenz B. (Frontiers in Psychiatry, 2022)
Background: Major depression is one of the leading causes of disability and limited capacity to work. Neuropsychological impairment is a common symptom in acute and remitted major depression and is associated with poor psychosocial functioning. This scoping review aimed to identify research on the role of neuropsychological functioning in outcomes of vocational rehabilitation programs in individuals with depression. Methods: We report on the conduct of this pre-registered (https://osf.io/5yrnf) scoping review in accordance with PRISMA-ScR guidelines. PubMed and PsychInfo were systematically searched for English or German research articles published between 1990 and September 2021 that studied objective neuropsychological tests as predictors of vocational rehabilitation interventions and included participants with depression. Results: The systematic literature search yielded no studies that specifically targeted subjects with major depression. However, eight articles published since 2016 were included in the review, analyzing data from five trials that evaluated the effectiveness of supported employment in North America and Europe in severe mental illnesses. An estimated 31% of the total number of participants included (n = 3533) had major depression. Using a variety of cognitive tests and covariates, seven articles found that neuropsychological functioning - especially global cognition scores, verbal and visual learning and memory - significantly predicted vocational outcomes of rehabilitation programs. Conclusion: Despite a lack of studies specifically targeting major depressive disorder, the identified literature suggests that higher baseline neuropsychological functioning predicts better vocational outcomes of supported employment programs in individuals with depression. In clinical practice, additional neuropsychological modules during return-to-work interventions might be helpful for vocational outcomes of such programs.